Nanotechnology: A Promising Approach for Delivery of Neuroprotective Drugs - Naqvi, Saba; Panghal, Archna; Flora, S. J. S. (Frontiers in Neuroscience, 2020)
Central nervous system (CNS) disorders especially neurodegenerative disorders are the major challenge for public health and demand the great attention of researchers to protect people against them. In past few decades, different treatment strategies have been adopted, but their therapeutic efficacy are insufficient and have only shown partial mitigation of symptoms and are further associated with severe adverse effects. Blood-brain barrier (BBB) and blood-cerebrospinal fluid barrier (BSCFB) guard the CNS from harmful substances and pose as the major challenges in delivering drugs into CNS for treatment of CNS complications such as Alzheimer’s disease, Parkinson’s disease, Huntington’s disease, stroke, epilepsy, brain tumors, multiple sclerosis, encephalitis, and many more. Nanotechnology has come out as an exciting and promising new platform of treating neurological disorders and has shown great potential to overcome problems related to the conventional treatment approaches. Molecules can be nanoengineered to carry out multiple specific functions such as to cross the blood-brain barrier, target specific cell or signaling pathway, respond to endogenous stimuli, and act as a vehicle for gene delivery, support nerve regeneration and cell survival. In present review, the role of nanocarrier systems such as liposomes, micelles, solid lipid nanoparticles, dendrimers, and nanoemulsions for delivery of various neurotherapeutic agents has been discussed, besides this, their mechanism of action, and nanoformulation of different neuroprotective agents like curcumin, edaravone, nerve growth factors in CNS disorders like Alzheimer’s, Parkinsonism, epilepsy, stroke and brain tumors has been reviewed.